A physico-chemical properties based model for estimating evaporation and absorption rates of perfumes from skin - Kasting, G.B.; Saiyasombati, P. (International journal of cosmetic science, 2001)
Synopsis Because of their potential for inducing allergic contact dermatitis (ACD) if used improperly, perfumes are carefully assessed for dermal safety prior to incorporation into cosmetic products. Exposure assessment for these materials often involves the conservative assumption of 100% absorption of each component. This report describes an improved method to estimate the absorption and evaporation of perfume ingredients from skin, based on their physico‐chemical properties. The effect of environmental variables such as temperature and wind velocity can be accounted for in a logical way. This was accomplished using a first‐order kinetic approach expected to be applicable for small doses applied to skin. Skin penetration rate was calculated as a fraction of the maximum flux estimated from the compound’s lipid solubility, Slip (represented by the product of octanol/water partition coefficient, Koctt, and water solubility, Sw), and molecular weight, MW. Evaporation rates were estimated from a modified Henry’s Law approach with a stagnant boundary layer whose thickness is a function of surface airflow, v. At a given value of v, evaporation rate was assumed proportional to the ratio Pvp/Slip, where Pvp is the vapour pressure of the ingredient at skin temperature, T. The model predicts a relationship for total evaporation from skin of the form %evap = 100x/(k+x) where x = PvpMW2.7/(KoctSw) and k is a parameter which depends only on v and T. Comparison with published data on perfume evaporation from human skin in vivo showed good agreement between theory and experiment for two closely related perfume mixtures (r2 = 0.52–0.74, s = 12–14%, n = 10). Thus, the method would seem to have a good prospect of providing skin absorption estimates suitable for use in exposure assessment and improved understanding of dose‐related contact allergy. Résumé Les parfums ont un fort potentiel allergique quand ils sont utilisés de manière inadéquate sur la peau. Pour cette raison, ils sont sujets à des tests rigoureux avant leur incorporation dans les produits cosmétiques. L’évaluation de l’exposition à ces matériaux repose souvent sur l’hypothèse que chaque composé est absorbéà 100%. Notre étude décrit une nouvelle approche pour affiner la détermination de l’absorption et l’évapouration des parfums et de leurs ingrédients à travers la peau, basée sur leurs propriétés physico‐chimiques. L’effet des variables liées au milieu ambient, comme la temperature et la vitesse de l’air, peut être introduit de manière logique en utilisant une cinétique du premier ordre, applicable a priori à de petites doses appliquées sur la peau. La vitesse de pénétration à travers la peau est calculée comme le quotient du flux maximum estiméà partir de la solubilité en phase lipide du composé, Slip (calculée comme le produit du coefficient de partage octanol/eau Koct, et la solubilité aqueuse, Sw), et du poids moleculaire, MW. Les taux d’évapouration sont calculés en utilisant une modification de la loi de Henry avec une couche stagnante dont l’épaisseur est une fonction des mouvements d’air à la surface, v. Pour une valeur donnée de v, le taux d’évapouration est supposéêtre proportionnel au quotient Pvp/Slip, ou Pvp est la pression de vapeur du composé a la température de la peau, T. Le modèle prédit une équation pour l’évapouration totale depuis la peau du type: %evap = 100x/(k+x) oùx = PvpMW2.7/(KoctSw) et k est une variable qui dépend seulement de v et de T. Pour deux parfums de compositions voisines, le modèle est en bon accord avec des données publiées sur l’évapouration de parfum depuis la peau in vivo (Corrélation théorie/expérience: (r 2 = 0.52–0.74, s = 12–14%, n = 10). En conclusion, cette méthode semble prometteuse pour fournir des estimations qui peuvent etre utilisées dans les évaluations d’exposition et pour permettre de mieux comprendre l’effet de dose dans l’allergie de contact.